PENGARUH MANAJEMEN INOVASI PROGRAM PENDIDIKAN MA-BATUTER (MANAJEMEN APLIKASI BACA TULIS TERTINTEGRASI CERITA) PADA PENDIDIKAN ANAK USIA DINI (PAUD) TAAMASA SUMBAWA - Tirta, Andy; Esabella, Shinta (Jurnal TAMBORA, 2020)
This study aims to examine differences in the management of innovation in the MABATUTER education program (Management of Integrated Reading and Writing Applications) for studentsmanagement conditions carried out by schools conventionally and digitally.The research method used was a qualitative before-after experiment, namelycompare the assessment of parents of students related to program managementMA-BATUTER education carried out conventionally with the after conditionimplementing digital applications developed independently byby PAUD TAAMASA Sumbawa. The research data were obtained from 10 sampling peopleparents of students using a score-based assessment instrument on the aspectread, write, and retell. To determine the effectiveness of different testsusing non-parametric statistics through Wilcoxon test, gain score test. Resultt-test research and gain score of MA-BATUTER education program with applicationdigital is proven to be effective in improving students' ability to understand the content of the storyand can retell the information received in order to trainintelligence sensors of children from an early age.